A New Electron Acceptor with meta‐Alkoxyphenyl Side Chain for Fullerene‐Free Polymer Solar Cells with 9.3% Efficiency. Issue 11 (17th August 2017) - Zhang, Zhenzhen; Feng, Liuliu; Xu, Shutao; Liu, Ye; Peng, Hongjian; Zhang, Zhi‐Guo; Li, Yongfang; Zou, Yingping
Abstract: A new small molecule acceptor, m‐ITIC‐OR, based on indacenodithieno[3, 2‐ b ]thiophene core with meta ‐alkoxyphenyl side chains, is designed and synthesized. The m‐ITIC‐OR film shows broader and redshift absorption compared to its solution and matched energy levels with a hexafluoroquinoxaline‐based polymer donor‐HFQx‐T. Here, polymer solar cells (PSCs) by blending an HFQx‐T donor and an m‐ITIC‐OR acceptor as an active layer deliver the power conversion efficiency (PCE) of 6.36% without any posttreatment. The investigations demonstrate that the HFQx‐T:m‐ITIC‐OR blend films possess higher and more balanced charge mobility, negligible bimolecular recombination, and nanoscale interpenetrating morphology after thermal annealing (TA) treatment. Through a simple TA treatment at 150 °C for 5 min, an impressive PCE of 9.3% is obtained. This efficiency is among one of the highest PCEs for additive free PSCs. This is the first time alkoxyphenyl side chain is introduced into nonfullerene electron acceptor; more interestingly, the new electron acceptor (m‐ITIC‐OR) in this work shows a great potential for highly efficient photovoltaic properties. Abstract : A new electron acceptor (m‐ITIC‐OR) with meta ‐alkoxyphenyl side chains is designed and synthesized. A power conversion efficiency of 9.3% is achieved in nonfullerene polymer solar cells, demonstrating that the meta ‐alkoxyphenyl side chain is promising for constructing a high‐performance electron acceptor due to its simplicity and low cost. m‐ITIC‐OR shows a great potential for photovoltaic applications.